The Political Impact of Chilean New Song in Exile - Mcsherry, P (SAGE PUBLICATIONS INC, 2017)
The musical movement known as Chilean New Song became a key mobilizing force in politics in the 1960s and early 1970s in Chile, inspiring, uniting, and motivating people in a common cause and articulating the dreams and hopes of masses of people for progressive social change. Similarly, the New Song movement in exile, after the 1973 coup, helped to generate and sustain the support and solidarity of Chilean exiles and foreign nationals around the world, speaking about the repression in Chile, communicating the ideals of the popular movements, and inspiring and strengthening solidarity movements in many countries.